The perception of speech modulation cues in lexical tones is guided by early language-specific experience - Cabrera, Laurianne; Tsao, Feng-Ming; Liu, Huei-Mei; Li, Lu-Yang; Hu, You-Hsin; Lorenzi, Christian; Bertoncini, Josiane (Frontiers in Psychology, 2015)
A number of studies showed that infants reorganize their perception of speech sounds according to their native language categories during their first year of life. Still, information is lacking about the contribution of basic auditory mechanisms to this process. This study aimed to evaluate when native language experience starts to noticeably affect the perceptual processing of basic acoustic cues (i.e., frequency-modulation (FM) and amplitude-modulation (AM) information) known to be crucial for speech perception in adults. The discrimination of a lexical-tone contrast (rising versus low) was assessed in 6- and 10-month-old infants learning either French or Mandarin using a visual habituation paradigm. The lexical tones were presented in two conditions designed to either keep intact or to severely degrade the FM and fine spectral cues needed to accurately perceive voice-pitch trajectory. A third condition was designed to assess the discrimination of the same voice-pitch trajectories using click trains containing only the FM cues related to the fundamental-frequency (F0) in French- and Mandarin-learning 10-month-old infants. Results showed that the younger infants of both language groups and the Mandarin-learning 10-month-olds discriminated the intact lexical-tone contrast while French-learning 10-month-olds failed. However, only the French 10-month-olds discriminated degraded lexical tones when FM, and thus voice-pitch cues were reduced. Moreover, Mandarin-learning 10-month-olds were found to discriminate the pitch trajectories as presented in click trains better than French infants. Altogether, these results reveal that the perceptual reorganization occurring during the first year of life for lexical tones is coupled with changes in the auditory ability to use speech modulation cues.